Gaps and Obstacles to Organ Donation in Brazil: A Literature Review - Oliveira, Ana Flávia Cunha Gomide de; Cardoso, Raphael Angeli de Barros; Freitas , Katiúscia Christiane; Lotte , Ewerson Jacobini; Lucas, Barbara de Lima (Brazilian Journal of Transplantation, 2023)
Objective: To explore the factors that hinder organ donation in Brazil. Methods: A literature review was carried out, seeking the main factors that hamper organ donation, using the following descriptors: organ referral, brain death, and intensive care. Results: 54 studies published in the last five years were found: PubMed (n=15), EMBASE (n=32), Lilacs (n=1), Mendeley (n=16) and SciELO (n=0). Family members’ refusal is the main difficulty in the organ donation process in Brazil. The systematization of organ capture and distribution and the efficiency of diagnosing brain death proved predictive factors for higher rates of family acceptance andefficiency in the process stages. Conclusion: Measures to systematize organ procurement and distribution and the health team’s training can benefit the Brazilian organ donation scenario.